Critical Examination on Malaysian Companies Consecutive Share Buy - Back Program - Tan, Hai Khoon (2010)
This research examines the extent of the share buy-back program by Malaysia main board companies from 2006 to 2009. From the data collected from the Bursa Malaysia\'s web pages, it is found that the share buy-back program has become a very popular corporate activity. Consistent with the prior research, companies spent huge amounts of cash in share buy-back during the bear market as compare to bull market.